Stepwise Reversal of Immune Dysregulation Due to STAT1 Gain-of-Function Mutation Following Ruxolitinib Bridge Therapy and Transplantation - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2021)
Purpose Patients with heterozygous gain-of-function (GOF) mutations in STAT1 frequently exhibit chronic mucocutaneous candidiasis (CMC), immunodeficiency and autoimmune manifestations. Several treatment options including targeted therapies and hematopoietic stem cell transplantation (HSCT) are available for STAT1 GOF patients but modalities and outcomes are not well established. Herein, we aimed to unravel the effect of ruxolitinib as a bridge therapy in a patient with sporadic STAT1 T385M mutation to manage infections and other disease manifestations. Methods Peripheral blood mononuclear cells were isolated from the patient prior to, during ruxolitinib treatment and 6 months after HSCT. IFN-beta-induced STAT1 phosphorylation/dephosphorylation levels and PMA/ionomycin-stimulated intracellular IL-17A/IFN-gamma production in CD4(+) T cells were evaluated. Differentially expressed genes between healthy controls and the patient prior to, during ruxolitinib treatment and post-transplantation were investigated using Nanostring nCounter Profiling Panel. Results Ruxolitinib provided favorable responses by controlling candidiasis and autoimmune hemolytic anemia in the patient. Dysregulation in STAT1 phosphorylation kinetics improved with ruxolitinib treatment and was completely normalized after transplantation. T(H)17 deficiency persisted after ruxolitinib treatment, but normalized following HSCT. Consistent with the impairment in JAK/STAT signaling, multiple immune related pathways were found to be dysregulated in the patient. At baseline, genes related to type I IFN-related pathways, antigen processing, T-cell and B-cell functions were upregulated, while NK-cell function and cytotoxicity related genes were downregulated. Dysregulated gene expression was partially improved with ruxolitinib treatment and normalized after transplantation. Conclusion Our findings suggest that improved disease management and immune dysregulatory profile can be achieved with ruxolitinib treatment before transplantation and this would be beneficial to reduce the risk of adverse outcome of HSCT.
Keywords: STAT1 gain-of function mutation; mucocutaneous candidiasis; autoimmunity; interferon stimulated genes; ruxolitinib; hematopoietic stem cell transplantation